2018
DOI: 10.1177/0265659018793697
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audiovisual speech training on the phonological skills of children with specific language impairment (SLI)

Abstract: We developed a computerized audiovisual training programme for school-aged children with specific language impairment (SLI) to improve their phonological skills. The programme included various tasks requiring phonological decisions. Spoken words, pictures, letters and written syllables were used as training material. Spoken words were presented either as audiovisual speech (together with the talking face), or as auditory speech (voice alone). Two groups (10 children/group) trained for six weeks, five days per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…This difference in the strength of relationship may have a number of explanations, including the different tasks used (alliteration and rhyme matching for the deaf children, phoneme deletion for the hearing children) or that auditory speech information is more critical as a foundation for phonological development in hearing children. Despite a slightly weaker relationship, the results for hearing children support and extend previous studies that show an association between speechreading and phonological awareness in hearing children (Heikkilä et al, 2017(Heikkilä et al, , 2018Kyle & Harris, 2011). These studies highlight the multimodal nature of speech processing and phonological development in both hearing and deaf populations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This difference in the strength of relationship may have a number of explanations, including the different tasks used (alliteration and rhyme matching for the deaf children, phoneme deletion for the hearing children) or that auditory speech information is more critical as a foundation for phonological development in hearing children. Despite a slightly weaker relationship, the results for hearing children support and extend previous studies that show an association between speechreading and phonological awareness in hearing children (Heikkilä et al, 2017(Heikkilä et al, , 2018Kyle & Harris, 2011). These studies highlight the multimodal nature of speech processing and phonological development in both hearing and deaf populations.…”
Section: Discussionsupporting
confidence: 86%
“…Visual speech perception also influences word form recognition (Weatherhead & White, 2017) and vocabulary development in hearing infants and children (Altvater-Mackensen & Grossmann, 2015;Erdener & Burnham, 2018;Jerger et al, 2018). In children with developmental language disorder, Heikkilä et al (2018) found that audiovisual speech perception training led to improvements on a nonword repetition task (used as a measure of phonological representations) in contrast to auditory-only training. These findings support the idea that visual information contributes to the development of phonological representations in hearing children.…”
mentioning
confidence: 99%
“…Meronen et al [38] proposed that SLI children experienced a weak McGurk effect and when signals to noise ratio decreased, SLI children could not rely on visual speech as typically developing children of the same chronological age. Heikkilä et al [39] showed that word level-lip reading is impaired in 7 years old children with SLI. Moradi et al [40] have suggested that audio-visual training reinforces the rout to phonological and lexical representation in a way that facilitates their further access.…”
Section: Assessment Of Visual Working Memory (Wm)mentioning
confidence: 99%
“…This type of training has been used to promote the auditory and/or audiovisual speech perception of hearing‐impaired individuals (e.g., Bernstein et al, 2014; Moradi et al, 2017) and to improve the production of syllable strings among stuttered and non‐fluent aphasic individuals through visual speech imitation (e.g., Fridriksson et al, 2012; Henry et al, 2018; Kalinowski et al, 2000; Lee et al, 2010). Motor‐oriented training, on the other hand, primarily focuses on correcting mis‐articulated speech‐sounds among individuals with speech disorders (e.g., Adler‐Bock et al, 2007; Heikkilä et al, 2018; McAllisterbyun et al, 2014; Preston et al, 2013, 2017) and typically use visual, especially visual‐lingual speech (i.e., images of tongue gestures), as visual illustrations of articulator gestures to assist the learning of speech‐sound articulation.…”
Section: Introductionmentioning
confidence: 99%